Rapid Fishery and Aquaculture Sector Diagnosis Using Fishery Performance Indicators in the Gaza Strip - World Bank (World Bank, Washington, DC, 2020)
This report is prepared with the objective of conducting a rapid diagnosis of the fisheries sector and establishing an overview of it in the Gaza Strip (GS). The fisheries and aquaculture sector in the GS have many challenges, including institutional structure, movement constraints of people and goods, degraded infrastructure, and deteriorating vessels. Despite various challenges, the sector has some promising characteristics. These include: (i) a relatively well-organized fishing industry, (ii) existing and emerging entrepreneurship in aquaculture, and (iii) a local knowledge base within the academic community in the GS. A rapid diagnosis and understanding of the current state of the fisheries sector is a first step towards potential future engagement. The fishery performance indicators (FPIs) were selected as the rapid sector assessment instrument for economic, community, and ecological outcomes of fisheries. The FPIs have been applied to different fisheries in different countries. In this report, the instrument was applied to overall fisheries, as opposed to specific fisheries, in the GS. As a prerequisite to applying FPI scoring, a descriptive fishery profile was developed.